1984
DOI: 10.1093/jnci/72.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cytotoxicity of Human Macrophages After Incubation With Synthetic Analogues of 2-Lysophosphatidylcholine2

Abstract: Human alveolar macrophages as well as macrophages derived from Teflon culture of blood-borne monocytes were incubated with synthetic analogues of 2-lysophosphatidylcholine and then tested for their cytotoxic capacity against an allogeneic lymphoma cell line. Metabolic, rather stable analogues enhanced macrophage cytotoxicity significantly. This phenomenon was shown both in a growth-inhibition assay as well as in the 51Cr release assay. Macrophage activation was dose- and time-dependent and was potentiated at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This confirms the results reported by other authors, who have demonstrated the leishmanicidal activity of different alkyl-lysophospholipids (Croft et al 1987(Croft et al , 1993(Croft et al & 1996. The differences in the low activity of the alkyl-lysophospholipids against the promastigotes with respect to the amastigotes can be accounted for by the fact that the alkyllysophospholipids strengthen the cytotoxicity of the macrophages and consequently aid in the death of the parasite within the infected cell, either by the direct action of the compounds or by the secondary effect on the host cells (Berdel 1980;Andreesen et al 1984;Daniel 1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This confirms the results reported by other authors, who have demonstrated the leishmanicidal activity of different alkyl-lysophospholipids (Croft et al 1987(Croft et al , 1993(Croft et al & 1996. The differences in the low activity of the alkyl-lysophospholipids against the promastigotes with respect to the amastigotes can be accounted for by the fact that the alkyllysophospholipids strengthen the cytotoxicity of the macrophages and consequently aid in the death of the parasite within the infected cell, either by the direct action of the compounds or by the secondary effect on the host cells (Berdel 1980;Andreesen et al 1984;Daniel 1993).…”
Section: Discussionsupporting
confidence: 90%
“…The effect of alkyl-lysophospholipids against tumour cells is largely studied, and the citotoxicity of edelfosine, miltefosine, and ilmofosie against macrophages was reported by many authors (Andreesen et al 1984;Schreiber et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ether lipids seem to be suited for purging residual malignant cells from marrows prior to autologous bone marrow transplantation (ABMT). During the early treatment studies, it became evident that the antineoplastic activity of some ALP analogs in vivo might be partially mediated by cytotoxic macrophages (Munder et al, 1977;Berdel et al, 1980;Andreesen et al, 1984). Assessing the importance of cytotoxic macrophages as mediators of ALP-effects, it could be shown that macrophages not only are cytotoxic in vitro to a variety of neoplastic cells after incubation with these lipids, but can be also used for successful treatment of syngeneic tumour and metastasis developd e ment in vivo.…”
Section: Precfinical Studiesmentioning
confidence: 99%
“…1,21,[33][34][35][36] As for the indirect effects, these substances have been reported to induce tumor cell differentiation and differentiation of myelomonocytic cells [13][14][15] and to activate macrophages. 10,16,17,[37][38][39] Since most of the studies dealing with HPC-mediated macrophage activation were performed in vitro, it was unclear until now in how far this mechanism substantially contributes to the antitumor effect that has been observed in several human tumor models. Already in earlier publications the assumption was discussed that the regression of human breast tumor growth in nude mice after treatment with alkylphosphocholines might be caused not only by a direct action to the tumor cells themselves but also by an interaction with the host's immune system and a probable macrophage activation.…”
Section: Discussionmentioning
confidence: 99%